Application of phased antenna arrays for pipeline leak detection; Journal of Petroleum Science and Engineering; Vol. 161 - Bolotina I. O. Irina Olegovna; Borikov V. N. Valery Nikolaevich; Ivanova V. S. Veronika Sergeevna; Mertins K. V. Kseniya Viktorovna; Uchaykin (Uchaikin) S. V. Sergey Victorovich (2018, 2018)
Title screen